2006
DOI: 10.1111/j.1553-2712.2006.tb00272.x
|View full text |Cite
|
Sign up to set email alerts
|

Rescuer Fatigue: Standard versus Continuous Chest-Compression Cardiopulmonary Resuscitation

Abstract: CCC-CPR resulted in more adequate compressions per minute than STD-CPR for the first 2 minutes of CPR. However, the difference diminished after 3 minutes, presumably as a result of greater rescuer fatigue with CCC-CPR. Overall, CCC-CPR resulted in more total compressions per minute than STD-CPR during the entire 9 minutes of resuscitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(16 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…Several investigations have also shown that improved outcomes are associated with greater chest compression depth [9,10]. The quality of chest compressions during CPR has been demonstrated to decline rapidly after a short period [11,12]. A number of simulations have shown that rescuers develop immediate fatigue during CPR and that chest compression depth declines after 1 to 3 minutes of CPR [12][13][14].…”
Section: Introductionmentioning
confidence: 97%
“…Several investigations have also shown that improved outcomes are associated with greater chest compression depth [9,10]. The quality of chest compressions during CPR has been demonstrated to decline rapidly after a short period [11,12]. A number of simulations have shown that rescuers develop immediate fatigue during CPR and that chest compression depth declines after 1 to 3 minutes of CPR [12][13][14].…”
Section: Introductionmentioning
confidence: 97%
“…Published data analyzing algorithm changes are often derived from animal or mathematical models, for feasibility reasons [8][9][10][11]. To compare the quality of basic life support under the changed ERC guidelines, we therefore conducted a series of trials with bystanders in a manikin model of cardiac arrest.…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of the current 2-min interval rescuer change strategy is to overcome the deleterious effects of rescuer fatigue. Since the Hightower report, many studies have investigated the effect of rescuer fatigue on the quality of chest compressions, but the results were inconsistent [3,7,[10][11][12][13]. The most controversial issue is the onset time of rescuer fatigue, which inevitably results in marked deterioration of chest compression quality, especially of compression depth.…”
Section: Discussionmentioning
confidence: 94%
“…The most controversial issue is the onset time of rescuer fatigue, which inevitably results in marked deterioration of chest compression quality, especially of compression depth. Some studies reported a significant decrease in compression depth within 1 min from starting CPR [4,7,10], whereas other studies reported no marked decline in compression quality until 2 min [3,14]. Although the 2005 CPR guidelines considered the possibility of early rescuer fatigue, the 2005 CPR guidelines placed more emphasis on the possible benefit of minimal interruption and therefore recommended the RC2 method [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation